On Permutation Rho-Transitive in Permutation Rho-Algebras - Sharqi, Moataz Sajid; Khalil, Shuker (Iraqi Journal of Science, 2024)
Some of the novel algebraic topics explored in this paper, like Permutation         -algebra, permutation edge, permutation -transitive, permutation -ideal, permutation -ideal, and permutation -subalgebra are discussed and looked into. Additionally, permutation -algebra, permutation -morphism, equivalence relation with its congruence classes and quotient permutation -algebras were defined with specific results relating to our unique notions that have been developed and examined.